2020
DOI: 10.1186/s12864-020-6670-5
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid transcriptome sequencing approach improved assembly and gene annotation in Cynara cardunculus (L.)

Abstract: Background: The investigation of transcriptome profiles using short reads in non-model organisms, which lack of well-annotated genomes, is limited by partial gene reconstruction and isoform detection. In contrast, long-reads sequencing techniques revealed their potential to generate complete transcript assemblies even when a reference genome is lacking. Cynara cardunculus var. altilis (DC) (cultivated cardoon) is a perennial hardy crop adapted to dry environments with many industrial and nutraceutical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…In addition, KEGG analysis demonstrated that myhc isoform and hsp74 were significantly enriched in the tight junction in this study, which was once considered to be tightly related to meat hardness ( 32 ). Regretfully, due to the homology differences in myosin heavy chain nucleotide sequences in fish and higher vertebrates and the reduced isoform discovery effect resulting from the short read-sequencing in the transcriptome ( 33 ), the subtypes ( myh1, myh2 , and myh4 ) of myosin heavy chain, fast skeletal muscle, could not be annotated in grass carp transcripts in this study and previous studies ( 34 ). Instead, the expression status of myhc isoforms presented in Figure 2E and the relation between meat hardness and myhc isoforms in Appendix Table 3 clearly supported that the myhc isoform profile affected muscle hardness.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, KEGG analysis demonstrated that myhc isoform and hsp74 were significantly enriched in the tight junction in this study, which was once considered to be tightly related to meat hardness ( 32 ). Regretfully, due to the homology differences in myosin heavy chain nucleotide sequences in fish and higher vertebrates and the reduced isoform discovery effect resulting from the short read-sequencing in the transcriptome ( 33 ), the subtypes ( myh1, myh2 , and myh4 ) of myosin heavy chain, fast skeletal muscle, could not be annotated in grass carp transcripts in this study and previous studies ( 34 ). Instead, the expression status of myhc isoforms presented in Figure 2E and the relation between meat hardness and myhc isoforms in Appendix Table 3 clearly supported that the myhc isoform profile affected muscle hardness.…”
Section: Discussionmentioning
confidence: 67%
“…The rapid development of these technologies has produced a large number of new tools and software that should be comprehensively evaluated to allow the scientific community to identify and choose adequately between them. Some open-source resources and repositories for long-read software and tools are available on GitHub ( , accessed on 1 August 2020) and on the long-read-tools.org database [ 4 ].…”
Section: Final Remarksmentioning
confidence: 99%
“…Thus, many other “-omics” are quickly adapting to these technologies, further improving the accumulated scientific knowledge obtained during the past decades using short-read sequencing methods. Although Illumina (short read) is still a widely used sequencing platform for transcriptomic studies, it has some technological limitations that can be overcome using long-read sequencing [ 2 , 3 , 4 ]. The main limitations of short-read sequencing are that assembled transcripts from short reads do not cover full-length transcripts in eukaryotic genomes, and PCR amplification bias can be introduced during library construction [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our pipeline aimed to generate a full-length mRNA transcriptome with reference level sequence accuracy from a variety of organ samples by processing PacBio long-reads that were hybrid error-corrected with Illumina paired-end reads from the same samples. Similar approaches have been used to generate high quality transcriptomes in other species ( Feng et al, 2019 ; Puglia et al, 2020 ), but this is the first of its kind in Atlantic salmon. The strategy and the main functions of the pipeline is illustrated in Figures 1 – 3 .…”
Section: Discussionmentioning
confidence: 99%